دور العالقـــات العامـــــ ة اإللكترونيــة في بنـــ اء صـــورة ذهنيـــة للمؤسســـات الناشئـــة - مهيدي, أمينة; صدوق, فاخت حفصة (كلية العلوم الاجتماعية, 2025)
شهد العالم خلال العقدين الآخرين تطورات متسارعة في مجال الرقمنة، مما دفع معظم الهيئات والمنظمات الى تبني هذا التحول الرقمي. وتعتبر العلاقات العامة من أبرز المجالات التي تأثرت بهذا التحول إذ أصبحت تعتمد على كل ما هو الكتروني ورقمي في تعزيز سمعة المؤسسات والتعريف بها وبناء هوية ايجابية عنها، خاصة المؤسسات الناشئة كونها مؤسسات تسعى لإثبات وجودها في السوق. وفي هذا الإطار جاءت دراستنا هذه لتسليط الضوء على دور العلاقات العامة الرقمية في تكوين الصورة الذهنية الايجابية حول المؤسسات الناشئة. من خلال طرح التساؤل التالي: • ما هو دور العلاقات العامة الرقمية في بناء الصورة الذهنية للمؤسسات الناشئة؟ بالاعتماد على المنهج الوصفي الاستقصائي، كما تم الاعتماد على المقابلة كأداة اساسية لجمع البيانات المطلوبة اضافة الى الملاحظة، وقسمت الدراسة الى ثلاث فصول، الفصل الأول خصص للعلاقات العامة الرقمية، الفصل الثاني خصص للصورة الذهنية أما الفصل الثالث خصص للمؤسسات الناشئة. واستخلصت الدراسة أن العلاقات العامة الرقمية أصبحت أداة محورية في تشكيل الصورة الذهنية للمؤسسات الناشئة كونها سريعة وسهلة الوصول الى الجمهور وأن المؤسسة "يسير" الناشئة تسعى جاهدة لاستغلالها في تزويد الجمهور بالمعلومات الكافية حول كل ما يخص المؤسسة بالإضافة الى الترويج لمنتجاتها وخدماتها المقدمة. Over the past two decades, the world has witnessed rapid developments in the field of digitization, which has prompted most organizations and institutions to adopt digital transformation. Public relations is one of the most prominent areas affected by this transformation, as it has become heavily dependent on digital and electronic means to enhance corporate reputation, increase visibility, and build a positive identity - especially for startups, which seek to establish their presence in the market. In this context, our study aims to highlight the role of digital public relations in shaping a positive mental image of startups by raising the following research question: • What is the role of digital PR in building the mental image of startups? This study is based on the descriptive method. The interview was used as a main tool for collecting data. In addition to observation, our study is divided into three chapters: the first chapter is dedicated to digital public relations, the second chapter is dedicated to the mental image, and the third chapter for emerging institutions. The study concluded that digital public relations has become an essential tool in shaping the mental image of startups, because it is fast and easily accessible to the public. Yessir startup strives to take advantage of it in order to provide the public with sufficient information about all aspects of the organization, in addition to promoting its products and services
مؤسســة يسيـــــر نموذجـــا
Keywords: علاقات عامة رقمية، الصورة الذهنية، المؤسسات الناشئة